EDUKASI PEMANFAATAN TOGA SEBAGAI MINUMAN HERBAL DAN SPRAY ANTI NYAMUK PADA MASYARAKAT DESA POHARA KEC. SAMPARA KAB. KONAWE - Sahidin Sahidin; Gusti Ray Sadimantara; Wahyuni Wahyuni; Fadhliyah Malik; Fahria Nadiryati Sadimantara; Rahmat Muliadi; Muhammad Israwan Azis; Jumriani Jumriani (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
Indonesia has an incredibly high level of biodiversity, which makes it rich in various potentially medicinal plants. One of these is the family medicinal plant (Sari and Andjasmara, 2023). TOGA is a homegrown cultivated plant known for its herbal medicinal properties. Herbal medicine is derived from plants and processed or extracted in such a way that it becomes a powder, pill, or liquid without the use of chemicals. As it is commonly known, herbal medicines can treat diseases with minimal side effects because they are made from natural ingredients (Wulandari et al., 2017). The purpose of this community service activity is to enhance the understanding and skills of the community in utilizing plants found in the yards of the local households in the Pohara village, Sampara Subdistrict, Konawe District. These plants can be used in the production of herbal products such as herbal drinks and mosquito repellent sprays. This community service involved 31 community leaders and local residents. The method employed for community service was active participation, starting with socialization, herbal product preparation, and focused discussion sessions with community interaction. As a result of the community activities in the Pohara village, there was an improvement in skills, increased knowledge about herbal preparations, and an enhanced understanding of how to produce herbal products that are of good quality, hygienic, and safe for consumption.